Severe multiple simultaneous immune-related adverse events in a patient with head and neck cancer. Issue 2 (April 2023) - Aoki, Kazuma; Hamamoto, Takao; Chikuie, Nobuyuki; Kono, Takashi; Taruya, Takayuki; Ishino, Takashi; Ueda, Tsutomu; Takeno, Sachio
Abstract: Nivolumab, an immune checkpoint inhibitor (ICI) against the programmed death-1 pathway, has been used for the treatment of recurrent metastatic head and neck cancer. However, the management of immune-related adverse events (irAEs), a unique side effect of ICI therapy, can be problematic. Although severe irAEs have been reported to result from multi-ICI therapy, we report a case of multiple severe irAEs caused by single-agent nivolumab treatment. Nivolumab was administered to treat a case of hypopharyngeal cancer recurrence. However, when first-line chemotherapy of nivolumab was replaced with a second chemotherapeutic agent because of insufficient effectiveness, the patient showed anorexia, dermatitis, and mucositis; upper gastrointestinal endoscopy yielded a diagnosis of irAEs. Additional examinations revealed simultaneous multiple irAEs, including hypothyroidism, dermatitis, eyelid conjunctivitis, tracheal mucositis, upper gastrointestinal ulcer, and type 1 diabetes. Since all symptoms improved after steroid treatment, the patient was treated with subsequent chemotherapy. However, he died from uncontrolled cancer recurrence. Thus, even a single ICI agent can cause life-threatening irAEs. Moreover, the management of irAEs requires early recognition and close multidisciplinary collaboration in accordance with the countermeasure manual.